Potential of methylene blue fluorescence angiography for multiple intraoperative tissue perfusion assessments in plastic and reconstructive surgery: current knowledge and prospects - Heuvelings, Danique J. I.; Hillege, Lars E.; Al-Taher, Mahdi; Schols, Rutger M. (Frontiers in Surgery, 2025)
The expansion of (minimally invasive) surgical techniques has led to the development of advanced tools, including high-definition visual systems and fluorescence-guided surgery (FGS), enhancing surgeons' performance and patient safety. FGS employs near-infrared light and fluorophores like indocyanine green (ICG) for intraoperative imaging to improve anatomical navigation and decision-making. Recently, an increasing number of fluorescence imaging systems have shown capability in visualizing methylene blue (MB), which has an excitation peak at 700 nm, and its potential role in perfusion assessment. A recent study has highlighted MB's advantage over ICG due to its shorter washout time, enabling repeated intraoperative perfusion assessments using a dose of 0.5 mg/kg in a porcine model. This characteristic may be particularly beneficial in plastic and reconstructive surgery involving free (chimeric) flaps, pedicled skin flaps, pedicled intestinal transplants, and mastectomy skin flaps, where perfusion assessment can be critical at multiple stages. Therefore, we highlight some examples of flap reconstructions in this technical note. Important to know, MB is considered safe within the therapeutic doses (<2 mg/kg). However, it is contraindicated in certain patients, including those who are pregnant, have renal insufficiency, are on specific serotonin medications and some rare deficiencies. As dual-wavelength fluorescence imaging systems compatible with both ICG and MB advance, there is growing interest in the potential of MB for (multiple) flap perfusion assessment(s) in plastic and reconstructive surgery, building on promising research in bowel perfusion.